2010
DOI: 10.1159/000271915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization and Analysis of the <i>SRD5A2 </i>Gene in Six Korean Patients with 5α-Reductase Type 2 Deficiency

Abstract: Aims: The aim of this study was to perform a 5α-reductase type 2 gene (SRD5A2) analysis in 6 Korean patients with external genitalia ranging from predominantly female to male in whom 5α-reductase type 2 deficiency was suspected. Patients: Six patients from five unrelated families participated, and all of their parents were non-consanguineous. Three patients presented with ambiguous genitalia at birth, and 2 were referred owing to delayed puberty. The other patient was presented incidentally during an operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 50 publications
7
30
1
Order By: Relevance
“…The p.G203S mutation on one allele found in all 3 patients was previously reported in patients from Mexico [15,16], Thailand [17] and Korea [18]. The same mutation was also reported previously in 8 Chinese hypospadia patients [19].…”
Section: Discussionsupporting
confidence: 77%
“…The p.G203S mutation on one allele found in all 3 patients was previously reported in patients from Mexico [15,16], Thailand [17] and Korea [18]. The same mutation was also reported previously in 8 Chinese hypospadia patients [19].…”
Section: Discussionsupporting
confidence: 77%
“…Though the first proposed value was 20, Walter et al suggested 8.5 after hCG stimulation as a much more reliable cutoff value [24,64,65]. However, in many instances, this method has failed as a good predictor and various other approaches have been proposed [22,39,41,45,49], urinary steroid profiling (UPS) and gene mutation analysis being two alternatives. Chan et al suggested that UPS results can be misinterpreted; thus, molecular [25,39,40] p.G115D/p.G115D 5 2.60 0.55 [22,39,41,42] analysis was considered the most effective diagnostic method also taking into account the small size of the gene makes the diagnostic procedure easier [50].…”
Section: Diagnosismentioning
confidence: 99%
“…However, equivocal or false-negative T/DHT results are not uncommonly reported (2)(3)(4)(5)(6). Alternative approaches in diagnosing 5ARD include the use of urinary steroid profiling (USP) (7 ) and mutational analysis of SRD5A2 (8 ).…”
Section: ␣-Reductase 2 Is a Membrane-bound Nadphdependent Microsomalmentioning
confidence: 99%